The View from the Back of the Band : The Life and Music of Mel Lewis - Smith, Chris, 1981- (Book collections on Project MUSE., 2014)
Mel Lewis (1929-1990) was born Melvin Sokoloff to Jewish Russian immigrants in Buffalo, New York. He first picked up his father's drumsticks at the age of two and at 17 he was a full-time professional musician. The View from the Back of the Band is the first biography of this legendary jazz drummer. For over fifty years, Lewis provided the blueprint for how a drummer could subtly support any musical situation.